Assessment of the consistency among global precipitation products over the United Arab Emirates - Ghebreyesus, D. (2020)
The objective of this study is to cross-validate and analyze the consistency of four global precipitation products from the GPCC, TRMM, WM, and CMORPH datasets over the UAE using a network of 53 rain gauges from 2000 to 2010. The study also identifies and calibrates the best statistically performing precipitation product as an essential climatic input for monitoring, forecasting, and modeling hydrologic applications over the UAE. Statistical analyses indicate that the TMPA V7 precipitation products record the highest overall agreement with the observational network. Within the UAE, areas that receive high rainfall and fall within the vegetated highlands (e.g., >250 m), provide the most promise for incorporating satellite precipitation into hydrologic monitoring, modeling, or water resource management.